CONSTRUCTION AND EXPRESSION OF RECOMBINANT CELLULASE FROM MARINE BACTERIUM Bacillus amyloliquefaciens IN Bacillus megaterium MS941 AS A HOST CELL - DEWI KURNIASIH (NIM: 20510041); Pembimbing : Zeily Nurachman, D.Sc, SARI
Cellulose -the largest source biomass on the earth- is a polymer of glucose linked by beta-1,4 glycosidic bonds. Cellulose biomass can be utilized as a source of renewable energy in the form of bioethanol. Cellulose can be hydrolyzed to glucose by cellulases. Cellulases are complex enzymes consisting of endoglucanase (EC 3.2.1.4) that hydrolyzes cellulose randomly, exoglucanase (EC 3.2.1.74 and EC 3.2.1.91) that degrade cellulose chain from reducing and non-reducing end, and beta-glucosidase (EC 3.2.1.21) that cleavages cellobiose to glucose. Nowadays, there is a suitable cellulase for degrading crystalline cellulose yet to be found. Our previous results showed that the gene encoding endoglucanase from the marine bacteria Bacillus amyloliquefaciens PSM 3.1 have been isolated and expressed in Escherichia coli BL21 (DE3). The endoglucanase exhibited an optimum temperature activity at 50 Ã‚ÂºC, pH 6, and 50% of remaining activity at a range of 40-60 oC. Furthermore, endoglucanase retained 90% activity in 2 M NaCl. Since endoglucanase secreted intracellularly and the activity was not so high, it was not suitable to be employed in industry. To obtain a recombinant cellulase that can degrade cellulose efficiently, genetic engineering works is essential to be carried out. The aim of the research is to construct recombinant cellulases expressed extracellularly in Bacillus megaterium MS941 as a host cell. Methods included isolation of beta-glucosidase gene; construction of cellulase gene fusion; determination of optimum condition for production of cellulase; characterization of recombinant cellulose, and characterization of cellulose degradation products by recombinant cellulase. The results showed that beta-glucosidase gene (bglZ) has been sequenced consisting of 1398 bp encoding 465 amino acid residues. The enzyme belongs to glycoside hydrolase 1 (GH 1) with the predicted catalytic residues on residues Glu171 and Glu364. To convert cellulose into glucose, at least two types of cellulases: endoglucanase or exoglucanase and beta-glucosidase are required. For the purpose, here four recombinant proteins: fusion-EglII-BglZ (fusion protein between endoglucanase and β-glucosidase), BglZ-EglII (coexpression of beta-glucosidase and endoglucanase), EglII, and BglZ were constructed in the expression vector pMM1525 and expressed in B. megaterium MS941. Of four recombinants, fusion-EglII-BglZ fusion was not expressed. The cells containing EglII recombinant that culture in modified medium containing 1% bacto peptone, 0.5% yeast extract, and 1% NaCl produced high enzyme activity after induction for 6 h. EglII recombinant had a KM of = 7.913 mM and Vmax of 0.384 mM min-1. The activity of EglII, BglZ-EglII and BglZ recombinants tested on various substrates: CMC (carboxy methyl cellulose), avicel (microcrystalline cellulose), and sugarcane bagasse showed that the only EglII recombinant was able to hydrolyze all substrates with the highest activity on soluble substrates pNPC and CMC. A mixture of recombinants: BglZ and EglII hydrolized avicel and sugarcane bagasse which produce reducing sugar of 4.161 (avicel concentration 20% (w/v)) and 4.692 (mu)mol (cellulose concentration 10% (w/v)) , respectively. Based on thin layer chromatography result, the recombinants: EglII, BglZ-EglII and mixture of BglZ and EglII hydrolized avicel to produce cellobiose and glucose.